2016
DOI: 10.1521/aeap.2016.28.6.524
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Safer Conception Counseling Toolkit for the Prevention of HIV: A Mixed-Methods Evaluation in Kisumu, Kenya

Abstract: Safer conception strategies can prevent HIV transmission between HIV-discordant partners while allowing them to conceive. However, HIV care providers in sub-Saharan Africa report they are not trained in safer conception, and patients are not routinely offered safer conception services. This mixed-methods pilot study evaluated the impact, acceptability, and feasibility of a novel Safer Conception Counseling Toolkit among providers and patients in Kenya. We enrolled 20 HIV-positive women, 10 HIV-discordant coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
2
15
0
2
Order By: Relevance
“…In the past decade, worldwide, there has been a steady increase in research, service delivery, and advocacy to support women living with HIV to make informed decisions about whether, when, and how to become mothers [1,3,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. National normative guidelines on safer conception have been issued in Canada [26], South Africa [9], and the United Kingdom [27], and the World Health Organization delineates strategies for achieving safe and healthy pregnancy in its guidelines on the sexual and reproductive health and rights of women living with HIV [10].…”
Section: Background/rationalementioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, worldwide, there has been a steady increase in research, service delivery, and advocacy to support women living with HIV to make informed decisions about whether, when, and how to become mothers [1,3,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. National normative guidelines on safer conception have been issued in Canada [26], South Africa [9], and the United Kingdom [27], and the World Health Organization delineates strategies for achieving safe and healthy pregnancy in its guidelines on the sexual and reproductive health and rights of women living with HIV [10].…”
Section: Background/rationalementioning
confidence: 99%
“…In addition, however, there is a need to ensure that services are prepared to address HIV-positive women's desire to have children in the future. Policymakers and service delivery organizations in Tanzania and elsewhere can consider building on existing national guidelines from South Africa, consensus statements from safer conception researchers and advocates for people living with HIV (PLHIV), and a safer conception toolkit that has been tested in Kenya, for instance [1,9,17]. In addition, once PrEP becomes available more widely, this may present an opportunity to test the acceptability of pre-conception PrEP for seronegative partners in mixed-status relationships.…”
Section: Plos Onementioning
confidence: 99%
“…One barrier to fully minimizing HIV transmission risk during peri‐conception is knowledge about safer conception options among individuals and providers and the initiation of discussion about these methods (individually and as a package) between providers and patients . Tools have been developed to empower providers to initiate discussions with couples about pregnancy plans and guidance from the World Health Organization promotes safer conception counselling . Yet prevailing community perspectives and assumptions about sexual and perinatal HIV transmission by people living with HIV prevent many individuals and couples from actively seeking safer conception counselling or services .…”
Section: Introductionmentioning
confidence: 99%
“…Those studies, along with our findings, highlight the urgent need for integrating family planning, and interventions for safer conception into HIV care and treatment [ 29 , 38 ]. Another study evaluated a Safer Conception Toolkit for HIV care and treatment providers and HIV discordant couples trying to conceive in Kenya [ 39 ]. A recent study in South Africa found high uptake of safer contraception methods suggesting that combination prevention methods are acceptable to clients and appropriate for scale-up [ 40 ].…”
Section: Discussionmentioning
confidence: 99%